Acute illness from Campylobacter jejuni may require high doses while infection occurs at low doses - Teunis, Peter F.M.; Bonačić Marinović, Axel; Tribble, David R.; Porter, Chad K.; Swart, Arno (Epidemics, 2018)
•This study generalizes infection and illness dose response relations for Campylobacter jejuni, accounting for variation in pathogen (strain) and host (immunity, species) characteristics.•Susceptibility to infection likely is high, requiring small doses to colonize.•In outbreaks illness occurs at low doses, while in challenge studies high doses may be required.•This can be explained by selection bias: outbreaks select for highly virulent strains, not propagated in culture, and hosts susceptible to developing detectable symptoms of acute illness.•Nonhuman primates cannot be shown to have higher susceptibility to campylobacteriosis than humans. Data from a set of different studies on the infectivity and pathogenicity of Campylobacter jejuni were analyzed with a multilevel model, allowing for effects of host species (nonhuman primates and humans) and different strains of the pathogen. All challenge studies involved high doses of the pathogen, resulting in all exposed subjects to become infected. In only one study a dose response effect (increasing trend with dose) for infection was observed. High susceptibility to infection with C. jejuni was found in a joint analysis of outbreaks and challenge studies. For that reason four outbreaks, associated with raw milk consumption, were also included in the present study. The high doses used for inoculation did not cause all infected subjects to develop acute enteric symptoms. The observed outcomes are consistent with a dose response effect for acute symptoms among infected subjects: a conditional illness dose response relation. Nonhuman primates and human volunteers did not appear to have different susceptibilities for developing enteric symptoms, but exposure in outbreaks (raw milk) did lead to a higher probability of symptomatic campylobacteriosis.